Introduction to technical services - Evans, G. Edward (Libraries Unlimited, 2002)
Used in library schools worldwide, this standard provides students with a thorough understanding of technical services. Updated and expanded, the 7th edition was carefully re-examined by the authors and includes a complete rewriting of the "Cataloging and Processing" section. The book covers all aspects of the field-from acquisitions to managing the cataloging department-with new emphasis on automation as it affects technical services work and those skills that can be developed through work experience or classroom instruction. Various automated acquisitions systems are described, and a detailed section on automated serials systems is included. Complete with helpful illustrations, statistics, and study guide questions, this text is a must for library and information science students!